Qualitative Research on Best Practices of UP Diliman Library Personnel in Community Outreach Projects during the Pandemic: To Provide Recommendations and Show the Current Practices of the Personnel during the Pandemic - Reina R. Irinco (Research Highlights in Language, Literature and Education Vol. 1, 2022)
Objective: This paper investigates the personal experiences of UP Diliman library personnel conducting community outreach projects, including (but not limited to) their challenges due to the pandemic. The study employs an Online Survey (Open-ended questions) through Google Forms. An online survey will be completed and will conclude with general recommendations and best practices drawn from the analysis of library staff/personnel experiences in UP Campus outreach projects. Methods: Online Survey (Open-ended questions) through Google Forms. Results: Librarians are active in outreach activities before and during the pandemic. During the pandemic, health protocols, travel restrictions, and social distancing prevent the librarians from fully engaging in these outreach activities—fear of being infected by the virus, coordination, and participation in LGUs. Difficulty in assessing which channels can best reach different community members, facilitating and engaging in projects due to limited mobility, travel bans, and delays in sending donations, fundraising is also problematic due to little face-to-face interactions. Time alignment and budget constraints are also a challenge. Following health protocols, prioritizing safety, coordination and partnership are the keys to a successful outreach program during this pandemic. No need to brag, help voluntarily and participate willingly in an organization without hesitation, and asking for anything in return is a realization in doing outreach activities. Social media and online distribution channels still allow us to help in any way we can. Information sharing can go a long way in helping those in need. Fulfillment in doing outreach activity, by just giving what you have is what you get by helping others. Recommendations: It might be good to investigate more local outreach programs in Metro Manila since it is one of the centers of the pandemic. Local front liners of UP, such as the security, janitors, and medical practitioners, also needs help. Comparisons to other university and organization outreach activities done by librarians and coordinators can also be studied and explored.